2021
DOI: 10.1007/s11357-021-00443-w
|View full text |Cite
|
Sign up to set email alerts
|

Serological and viral genetic features of patients with COVID-19 in a selected German patient cohort—correlation with disease characteristics

Abstract: To study host-virus interactions after SARS coronavirus-2 (SARS-CoV-2) infection, genetic virus characteristics and the ensued humoral immune response were investigated for the first time. Fifty-five SARS-CoV-2-infected patients from the early pandemic phase were followed up including serological testing and whole genome sequencing. Anti-spike and nucleocapsid protein (S/N) IgG and IgM levels were determined by screening ELISA and IgG was further characterized by reactivity to S-subunit 1 (anti-S1), S-subunit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…Moreover, it is showed that persons who reached threshold values for CCP donorship acceptance are older than candidates who were declined (40 vs. 36 years). Similar findings concerning Ab reactivity in relation to the age group were reported for COVID-19 convalescents from Germany [ 52 ], Brazil [ 19 ], US [ 20 , 53 ], England [ 21 ] and Austria [ 54 ].…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Moreover, it is showed that persons who reached threshold values for CCP donorship acceptance are older than candidates who were declined (40 vs. 36 years). Similar findings concerning Ab reactivity in relation to the age group were reported for COVID-19 convalescents from Germany [ 52 ], Brazil [ 19 ], US [ 20 , 53 ], England [ 21 ] and Austria [ 54 ].…”
Section: Discussionsupporting
confidence: 78%
“…Considering individual comorbidities, some studies have shown that anti-SARS-CoV-2 IgG levels show a positive correlation with obesity [ 62 ] and IgM with the presence of tumor diseases [ 52 ] due to probable impaired cellular anti-SARS-CoV-2 response. In addition, it is previously reported that comorbidities can lead to an increased level of proinflammatory cytokines which can have a stimulatory effect on humoral response [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, another study did not identify association between antibody levels and age of the seropositive individuals [10] , [11] . Despite the lack of consistent data regarding the production of anti-SARS-CoV-2 antibodies and the age of the infected individuals, other recent published studies showed that infected children and adults have differential antibody production, the latter having higher circulating levels of IgG [12] and that SARS-CoV-2 IgG levels are positively correlated with age in adult COVID-19 patients [13] , [14] , [15] , [16] . Additionally, the repertoire of recognized viral antigens appears to be larger in adults.…”
Section: Discussionmentioning
confidence: 99%
“…Among cohort and cross-sectional studies assessing associations between binding SARS-CoV-2 antibodies and BMI, the majority found positive associations between BMI and antibody levels [ 45 , 46 , [54] , [55] , [56] , [57] , [58] ] or seropositivity [ [59] , [60] , [61] , [62] , [63] ]. The remaining showed null associations between BMI and antibody levels [ [64] , [65] , [66] ], seropositivity [ 67 , 68 ], or both [ 49 ].…”
Section: Prevaccination Eramentioning
confidence: 99%